(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
The numerous activities carried out at Wawanrafi dam and farm site requires that a study of the aftermath of such activities be investigated. This study is aimed at determining the levels of heavy metals in some selected commonly consumed fruits (mango and guava) grown in the vicinity of the dam and in Kazaure market place. The levels of cadmium, copper, chromium and iron were determined in the edible and non-edible parts of mango, (Mangifera indica) and guava (Psidium guavaja) grown in Wawanrafi village and Kazaure market, Kazaure, Jigawa state Nigeria and in the soil where they are cultivated and the in the water used in irrigating the crops using atomic absorption spectrophotometric analysis, AAS techniques. The results revealed the heavy metal burden such as Cd, Cr, Cu and Fe in mango parts, seed, skin and pulp are in the range 0.2466 – 0.7500µg/g; 0.1660 – 0.9000µg/g and 0.4333 – 2.2170µg/g respectively. The ranges of concentration of heavy metals in various parts of guava such as seed, skin and pulp are 0.2570 – 1.5300 µg/g; 0.2570 – 1.133µg/g and 0.3600 – 1.1770µg/g. The findings reported the following ranges for Kazaure market fruits samples parts viz a viz seed, skin and fleshy pulp: Kazaure market guava fruit sample, KMGFS, 0.0827 – 0.8340µg/g, 0.1960 – 0.6410µg/g & 0.2670 – 1,017µg/g and Kazaure market mango fruit sample, KMMFS, 0.0836 – 0.611µg/g, 0.0450 – 0.7460µg/g & 0.0853 – 0.726µg/g. The results also show that on the whole plant basis, guava concentrated more of Cd and Cu than mango, while mango has higher levels of Cr and Fe than guava. Chromium is least detected in the pulp of guava. It could be concluded that mango and guava obtained in Wawanrafi village contained the heavy metals in variable proportions due to different activities such as fertilizer application, irrigation with dam water, coupled with other human activities like fishing, washing of clothes, vehicles and motorcycles, tourism. The heavy metal levels were lower than the WHO maximum limit, hence the fruit crops are considered safe for consumption.